Comparative genome-wide phylogenetic and expression analysis of SBP genes from potato (Solanum tuberosum). (April 2017) - Kavas, Musa; Kızıldoğan, Aslıhan Kurt; Abanoz, Büşra
Graphical abstract: Highlights: Identified 15 members of SBP in potato, that showed resemblance to Arabidopsis SBP -box genes. Found to be distributed in nine chromosomes and eight of them included miR156 and miRNA157 target sites. Expression pattern of StSBP was confirmed in the context of early flowering response. Abstract: Flowering time is a very important phase in transition to reproductive stage of life in higher plants. SQUAMOSA promoter-binding protein (SBP) gene family encodes plant-specific transcription factors that are involved in regulation of several developmental processes, especially flowering. Although SBP -box genes have been identified in different plants, there have been no study indicating the regulatory effect of SBP box in potato flowering. Here, we report for the first time the identification and characterization of SBP-box transcription factors as well as determination of expression level of SBP -box genes in Solanum tuberosum L. an important crop worldwide. Fifteen different SBP-box transcription factor genes were identified in potato genome. They were found to be distributed in nine chromosomes and eight of them included miR156 and miRNA157 target sites. Characterization of amino acid sequences were performed and protein interactions were predicted. In addition, expression levels of five S. tuberosum SBP -box genes were analysed by both in silico and qRT-PCR. All these results provide a better understanding of functional role of SBP -box gene family members in flowering time in potato.